Teste de tipo de um sistema de dosimetria TL para monitoração individual de fótons em Hp(10) (Brazilian Journal of Radiation Sciences (BJRS), 2018)
Although regulated, the use of HP(10) to estimate the effective dose of photons has not yet been implemented in Brazil. The operational quantity used in the country, temporarily, is the photon dose equivalent (Hx). For the external monitoring of individuals exposed to photons, the IRD uses an automatic TL dosimetry system with individual MTS-N monitors from the RADOS manufacturer, which contains LiF: Mg, Ti TLDs. The objective of this work was to characterize this system for the evaluation of the operational quantity HP(10). The measuring range is 0.2 mSv to 2 Sv, for photon energies from 20 keV to 1250 keV. The type test was done through performance tests for the following characteristics: homogeneity of the monitors, system reproducibility, linearity, temperature and humidity effect, energy and angular dependence, and fading. The acceptance requirements were taken from IEC 62387 standard and IRD-RT 002.01/95 technical regulation. The results show that all requirements have been met, except for the N-25 quality, at the angle of 60°.